Exploring the diverse therapeutic benefits of metformin: from anti-cancer to anti-inflammation and PCOS management - Nurul Azizah; Annisa Abdi Ghifari; Wirawan Adikusuma; Darmawi; Muhammad Yulis Hamidy (Creative Pharma Assent, 2024)
Background: Metformin is widely prescribed for type 2 diabetes mellitus and is recognized for its therapeutic benefits beyond glycemic control. This review summarizes current data on metformin's diverse roles in various therapeutic contexts, including treating polycystic ovarian syndrome (PCOS), anti-inflammatory effects, and cancer prevention. Method: This comprehensive examination highlights the multifaceted applications of metformin in modern medicine and its potential to enhance the treatment of inflammatory diseases, cancer, and reproductive disorders. Results and Discussion: Metformin's anti-inflammatory properties may benefit autoimmune disorders, neurological diseases, and cardiovascular illnesses. In women with PCOS, metformin aids in restoring menstrual regularity, inducing ovulation, and improving reproductive outcomes by enhancing insulin sensitivity, modulating ovarian function, and reducing hyperandrogenism. Additionally, emerging evidence suggests that metformin may reduce cancer incidence and mortality in diabetic individuals by modulating cellular metabolism, inducing apoptosis, and inhibiting tumor cell proliferation. Conclusion: Our review suggests promising evidence for metformin's role in cancer prevention, reducing inflammation, and managing PCOS. However, further research is required to identify patient subgroups that will benefit most from metformin therapy, elucidate its mechanisms of action, and optimize dosing regimens.